2016
DOI: 10.3109/0886022x.2016.1160207
|View full text |Cite
|
Sign up to set email alerts
|

Sclerostin levels in uremic patients: a link between bone and vascular disease

Abstract: Sclerostin is a marker of low-turnover bone disease in end stage renal disease patients. The aim of this study was to evaluate serum sclerostin in uremic patients, analyzing its behavior during a single hemodialysis session. Twenty-one adult patients on intermittent hemodialysis treatment were enrolled. Acetate Free Bio-filtration (AFB) was the technique employed. Uremic patients were characterized by higher levels of serum sclerostin when compared with values observed in healthy subjects. Sclerostin assessed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 17 publications
1
9
0
3
Order By: Relevance
“…They concluded that the decrease in sclerostin level was associated with Kt/V [44]. We also observed a similar negative association between sclerostin level and Kt/V.…”
Section: Discussionsupporting
confidence: 74%
“…They concluded that the decrease in sclerostin level was associated with Kt/V [44]. We also observed a similar negative association between sclerostin level and Kt/V.…”
Section: Discussionsupporting
confidence: 74%
“…Недавние сообщения позволяют предполагать, что высокий уровень склеростина способен отражать сниженный костный метаболизм и может быть полезным как маркер низкообменной костной болезни на продвинутых стадиях ХБП [19]. Как антагонист Wnt/β-катенин-сигнального пути, который вовлечен в биологию сосудов, склеростин может быть вовлечен в сосудистую кальцификацию [20]. Кроме того, сообщалось, что склеростин может быть ассоциирован с клиническими исходами, однако результаты противоречивы [20,21].…”
Section: ââåäåíèåunclassified
“…In this study, the best cutoff values obtained for serum sclerostin as a potential biomarker for both types of calcification revealed that sclerostin was more of a sensitive rather than a specific biomarker. Bruzzese et al [30] reported serum sclerostin as a reliable biomarker of VC based on a ROC curve generated cutoff value of 1.15 ng/mL (50.6 pmol/L). As regard valvular calcification, the present study to the best of our knowledge was the first to use ROC curve modality in addressing the sensitivity and the specificity of serum sclerostin as a potential biomarker of valvular calcification.…”
Section: Discussionmentioning
confidence: 99%